Geochemical characteristics of two types of early Paleozoic granitoids from the Soer Rondane Mountains, East Antarctica - Li, Zilong; Tainosho, Yoshiaki; Shiraishi, Kazuyuki; Owada, Masaaki; Kimura, Jun-ichi (National Institute of Polar Research, 2001)
P(論文) Early Paleozoic granitoids of the S0r Rondane Mountains, which occur as stocks, batholiths or sheets and intrude into late Proterozoic high- to intermediate-grade metamorphic rocks, represent prominent Pan-African to post Pan-African intermediateacidic magmatic events. They are mainly composed of granite and syenite and are enriched in alkalis. Based on geochemical features, there are two types of early Paleozoic granitoids: (1) volcanic-arc type (including Dufek and Lunckeryggen) granitoid, and (2) within-plate type (including Austkampane, Pingvinane, Vikinghogda and Rogerstoppane) granitoid. The volcanic-arc type granitoid has higher Mg#, Sr, and Sr/Ba, Sr/Y, La/Sm, La/Yb and LREE/HREE ratios, lower A/CNK and Ga/Al ratios, and ΣREE with no or positive Eu anomalies. On the other hand, the within-plate type granitoid has relatively higher A/CNK and Ga/Al ratios, and ΣREE, lower Mg#, Sr, and Sr/Ba, Sr/Y, La/Sm, La/Yb and LREE/HREE ratios with moderate to strong negative Eu anomalies. Geochemical characteristics as well as isotopic data of two types of early Paleozoic granitoids indicate two possibilities of their petrogenesis. One is that the volcanic-arc type granitoid may have been derived from deeper parental magma source by process of fractional crystallization with or without assimilation and/or mixing, subsequently, successive fractional crystallization from the same magma source (should be altered components) after assimilation by crustal materials during ascending, to produce the within-plate type granitoid; the other is that they are derived from different source materials and have different processes. The volcanic-arc type granitoid may be derived from partial melting of the Nils Larsen tonalite with minor mixing with, for example, host gneisses, while the within-plate type granitoid is formed by assimilation of crustal materials of host metamorphic rocks by the melt and then fractional crystallization. departmental bulletin paper